2015
DOI: 10.1186/s12974-015-0382-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of neonatal rats to alcohol has differential effects on neuroinflammation and neuronal survival in the cerebellum and hippocampus

Abstract: BackgroundFetal alcohol exposure is a leading cause of preventable birth defects, yet drinking during pregnancy remains prevalent worldwide. Studies suggest that activation of the neuroimmune system plays a role in the effects of alcohol exposure during the rodent equivalent to the third trimester of human pregnancy (i.e., first week of neonatal life), particularly by contributing to neuronal loss. Here, we performed a comprehensive study investigating differences in the neuroimmune response in the cerebellum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 101 publications
(107 reference statements)
3
124
0
Order By: Relevance
“…Interestingly, TGF-β was not affected by AE at either time point, in contrast to our previous report of increased levels following PD4–9 AE. Recent work by Topper et al (2015) also reported no changes in TGF-β expression in the male rat hippocampus following a PD3–5 alcohol exposure. It is possible that a more prolonged exposure to alcohol is needed to elicit a TGF-β response.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, TGF-β was not affected by AE at either time point, in contrast to our previous report of increased levels following PD4–9 AE. Recent work by Topper et al (2015) also reported no changes in TGF-β expression in the male rat hippocampus following a PD3–5 alcohol exposure. It is possible that a more prolonged exposure to alcohol is needed to elicit a TGF-β response.…”
Section: Discussionmentioning
confidence: 93%
“…In the healthy developing brain, microglia are involved in many necessary, normal development processes including the culling of apoptotic cells, synaptic pruning, and masculinization of the brain and behavior (Dalmau et al 1998; Bessis et al 2007; Paolicelli et al 2011; Lenz et al 2013). Following identification of a pathogen, microglia respond by changing their phenotypic activation state to increase production of pro-inflammatory cytokines (Kreutzberg 1996; Hanisch 2002; Town et al 2005; Neumann et al 2008; Kane et al 2011; McClain et al 2011; Topper et al 2015; Boschen et al 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in microglia activity and increases in pro-inflammatory cytokines are thought to both result from and contribute to alcohol pathologies [3,4]. The effects of alcohol exposure on the immune system are complex, and adding to this complexity is the fact that microglia can function in different contexts as either neuroprotective or cytotoxic agents [5].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol induces a number of changes in the immune system, generally resulting in a proinflammatory state in the CNS [4,[15][16][17][18]. For example, alcohol has been shown to stimulate toll-like receptor 4 (TLR4) and toll-like receptor 2 (TLR2) expression in microglia, thereby increasing pro-inflammatory mediators, reactive oxygen species, and neuronal apoptosis [8,9,19].…”
Section: Introductionmentioning
confidence: 99%